The linguistics characterstics of Bni Sofyan`s dialect: An analytic descriptive study - Al-salmi, Afrah Mohsen (Arab Journal for Sciences and Research Publishing, 2019)
The study aims at monitoring the manifestations of the change in the dialects and trying to monitor the vocabulary of the tone of Sufian and studying it in a voice، morphological، and sedative manner، and indicating how different it is from the dialects in Taif، which is its original home. The study society is one of the tribes of Taif، The study of the descriptive approach of the analytical structure، and the related literature as a method of study. The study reached several results، the most important of which were: The tone of Bani Sufyan contains clear words، the dialect retained the phenomena of language Which is characterized by classical Arabic، and this shows us that it is an integral part of the language، and that its study reveals phenomena that are no longer used in contemporary classical، the geographical environment of the region contributed to the preservation of the members of the tribe manifestations of the dialect، contrary to the classical language in some words، That this difference to a particular development has an impact on its origin may be revealed by the next studies، singled out the scar pattern، and attach E silence or E break as the old scientists، compared to the dialects of the neighboring tribes، the linguistic phenomena observed in the dialect keep the sign Arab Present verb p Colonic (written) and (planted)، a manifestation of the manifestations of classical Arabic، the study recommended that many of the most important recommendations، language studies with interest apposition dimension of knowledge of its importance and the growing interest of it.
Keywords: Arabic dialects; The Banu Sufyan tribe; Linguistic studies; Syntactic dimension